Pasang Surut Hubungan Agama-agama Jawa - Jamhari Jamhari (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2000)
This book is the most recent publication presenting an anthropological study on the Javanese religion and culture. The seminal work of Clifford Geertz, The Religion of Java (1960), seems to have inspired a number of scholars to study further the complex entities of Javanese religion. The book of Mark Woodward, Islam in Java: Normative Piety and Mysticism in the Sultanate of Yogyakarta (1989), is one of the scholarly works inspired by the division of Javanese religion by Clifford Geertz into abangan, santri and priyayi. The same topic can also be found in the work by Robert Hefner, Hindu Javanese: Tengger Tradition and Islam (1985). However, different from Clifford Geertz who holds the opinion that Javanese religion-albeit plural in an appearance-is basically established on the basis of Hindu-Buddhist, religion the two mentioned scholars state that Islam in an important basis of the Javanese religion.DOI: 10.15408/sdi.v7i1.720